Can Platelet Mass Index Be a Parameter to Predict Intraventricular Hemorrhage in Very-Low-Birth-Weight Newborns? - Korkmaz, Levent; Bastug, Osman; Ozdemir, Ahmet; Ceylan, Mahir; Gunes, Tamer; Ozturk, Mehmet Adnan; Korkut, Sabriye (American Journal of Perinatology, 2019)
Objective Intraventricular hemorrhage (IVH) is an important problem in neonatal units not only in terms of its consequences but also its follow-up and the prediction of its emergence in newborns. In this study, we have compared platelet parameters such as platelet count (PC), mean platelet volume (MPV), and platelet mass index (PMI) in terms of IHV in very-low-birth-weight (VLBW) newborns. Thus, we have tried to determine platelet values to guide clinicians in both the prediction and follow-up of IVH.Study Design This is a retrospective, multicenter, and case-controlled study. In this study, 386 cases of VLBW newborns (below 1,500 g) and gestational age below 32 weeks, hospitalized and monitored between August 8, 2012, and April 7, 2018, were included. The platelet values of the cases on their 12th hour postpartum (PC1, MPV1, and PMI1) and the platelet values on days 5 to 7 (PC2, MPV2, and PMI2) were recorded in their study cards. A p-value of <0.05 was accepted as statistically significant.Results While there was no difference of PC1, MPV1, PMI1, PC2, or MPV2 values (p > 0.05), PMI2 values in the severe stage IVH group cases were found to be significantly lower compared with other platelet parameters (p < 0.05).Conclusion PMI2 values can provide clinicians with important knowledge that may aid them in recognizing important pathologies such as IVH.
Keywords: very-low-birth-weight newborn; intraventricular hemorrhage; platelet values; mean platelet volume; platelet mass index